El rincón de construcción en el desarrollo de la inteligencia lógica matemática en niños de 3 a 4 años de edad del Centro de Educación Inicial Carlota Noboa de Durango, provincia Bolívar, cantón Guaranda, periodo 2025 - Ambi Vinueza, Angie Gisella (2025)
This research analyzes the importance of the construction corner on the development of logical-mathematical intelligence in children aged 3 to 4 years at the Carlota Noboa de Durango Early Education Center in Guaranda, Ecuador, during the 2025 school year. The objective was to analyze the importance of this pedagogical space in strengthening skills such as classification, seriation, spatial relationships, and problem solving. The research was conducted using a qualitative approach, with a non-experimental, descriptive, bibliographic, and field design, using non-participant observation and a checklist applied to 20 children. The results showed that most children are at initial levels or in the process of developing logical-mathematical skills, reflecting the need for more structured activities. It is concluded that the construction corner, when used with pedagogical intent, promotes meaningful learning and logical thinking from an early age; therefore, a teaching guide with playful strategies is proposed to strengthen these skills.